2008
DOI: 10.1007/s11604-008-0270-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rice body formation accompanying the chronic nonspecific tenosynovitis of flexor tendons of the wrist

Abstract: Rice body formation is generally a rare disorder related to rheumatoid arthritis. It can also be observed in cases of systemic lupus erythematosus, seronegative arthritis, infectious arthritis (tuberculosis, atypical mycobacterial infection), nonspecific arthritis, and osteoarthritis. It is generally located within joints or bursae. Multiple rice bodies of tendon sheaths are rarely encountered. Rice body formation may also be encountered without underlying systemic disorders. We present a case of multiple rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…[3][4][5][6][7] However, rice bodies in tendon sheaths are rarely seen among non-tuberculosis patients. 8,9 The pathogenesis of rice body formation has not yet been completely determined. Several theories exist regarding the formation of rice bodies including micro-infarction of the synovium with release of tissue into the joint, 3 chronic bursitis, 10 encasement of synovial shedding following inflammation, 11 encasement of fibrin 12 and alteration in viscosity and content of synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] However, rice bodies in tendon sheaths are rarely seen among non-tuberculosis patients. 8,9 The pathogenesis of rice body formation has not yet been completely determined. Several theories exist regarding the formation of rice bodies including micro-infarction of the synovium with release of tissue into the joint, 3 chronic bursitis, 10 encasement of synovial shedding following inflammation, 11 encasement of fibrin 12 and alteration in viscosity and content of synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis of compound palmar ganglion includes inflammatory arthritis (rheumatoid arthritis, gouty arthritis), sarcoidosis, infective (pyogenic infections, foreign body tenosynovitis, fungal granuloma) and other lesions of the tendon sheath (pigmented villonodular synovitis, giant cell tumour, amyloidosis and synovial chondromatosis). 2,3,15,16 The diagnosis can be confirmed by open excision biopsy with histopathological examination and mycobaterial culture of the specimen. Lertsrisatit et al 17 reported the sensitivity of synovial fluid AFB staining (32%), culture (80%), histology(65%), PCR(63%) and concluded that PCR can be used as an early diagnostic tool 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that they can be found around the tendon sheaths, but this is a rare occurrence related to rheumatoid arthritis (RA) [14] in which they can be seen within the joints or bursae. In addition, rice bodies can also be observed in cases of systemic lupus erythematosus (SLE), seronegative arthritis, infectious arthritis (TB, atypical mycobacterial infection) nonspecific arthritis, and osteoarthritis (OA).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rice bodies can also be observed in cases of systemic lupus erythematosus (SLE), seronegative arthritis, infectious arthritis (TB, atypical mycobacterial infection) nonspecific arthritis, and osteoarthritis (OA). [14][15][16][17][18][19] However, Woon et al [20] reported that finding rice bodies along with millet seed or melon seed-shaped lesions is highly suggestive of tuberculous tenosynovitis. They also suggested that the surgeon has to be aware of the significance of loose bodies when performing a routine excision of innocuous looking wrist ganglia.…”
Section: Discussionmentioning
confidence: 99%